Silk-Magnesium Composite Based Orthopedic Wire for Toe Fusion Surgery: Balancing Biodegradability and Preserving Native Toe Orientation - Day, Emily. (Tufts University. Tisch Library., 2024)
Thesis (M.S.)--Tufts University, 2024.; Submitted to the Dept. of Biomedical Engineering.; Advisor: David Kaplan.; Committee: Samuel Lin, and Chunmei Li.; Keywords: Biomedical engineering, Materials Science, and Biomechanics.